2007
DOI: 10.1590/s0044-59672007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Haematophagic behavior in laboratory of Lutzomyia cruzi (Mangabeira) (Diptera: Psychodidae) in relation to three mammalian blood sources in Manaus, Brazil

Abstract: The sand fly Lutzomyia cruzi is considered as one of vectors of visceral leishmaniasis in Brazil. This work examined optimum feeding age, feeding time, host preference, fecundity rates, and female blood meal volume taken by single females from a closed colony of L. cruzi. Mean feeding time was longer on hamsters, 6.6 minutes, than on humans, 5.7 minutes. 49.1% of the 48h-old flies fed on humans and 43.3% of 72h-old flies fed on hamsters. Of a total of 120 females, 61% fed on humans and 25% fed on hamsters. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Inside the residences with the highest number of collected insects were, in addition to the residents, there were dogs. This species is eclectic with regard to food habits 50 , which may have favored their collection inside the residences.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the residences with the highest number of collected insects were, in addition to the residents, there were dogs. This species is eclectic with regard to food habits 50 , which may have favored their collection inside the residences.…”
Section: Discussionmentioning
confidence: 99%
“…longipalpis obtained from Jequié, state of Bahia, Sobral and Massapé, state of Ceará and Teresina, PI, Afonso et al (2012) detected positive reactions in various animals, predominantly birds (36% in Jequié, 67% in Teresina, 29% in Sobral and 51% in Massapê), using the ELISA method. Chagas et al (2007) studied the haematophagous behaviour of Lu . cruzi bred in the laboratory and found that the females fed more easily on and preferred humans to hamsters when both sources of food were offered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…A ocorrência de casos humanos e a presença do L. cruzi, tendo em vista que as fêmeas desta espécie alimentam-se mais facilmente e preferencialmente em humanos 12 , a ocorrência de cães positivos e a ausência de L. longipalpis no município, bem como a detecção de infecção natural por L. (L.) infantum chagasi, evidenciam a participação de L. cruzi na transmissão da LV em Jaciara/MT.…”
Section: Foram Identificados 3110 Espécimes Pertencentes Aos Gênerosunclassified